PENGARUH KONSELING KEOMPOK TEKNIK REFRAMING TERHADAP PROKRASTINASI AKADEMIK SISWA KELAS X SMK SUNAN AMPEL TAHUN AJARAN 2022/2023 - Safitri, Liana; Mutakin, Fakhruddin; Budiono, Arifin Nur (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
The diverse learning behavior of students certainly affects the success rate obtained. Good learning behavior can be realized if students are aware of their responsibilities as a student. When students are motivated to learn, it often stops at the cognitive level, so when it comes to concrete action, the student often does the opposite. That is, students tend to postpone what is usually done at that time for various reasons so that the time they have is not managed properly. A behavior that is carried out repeatedly deliberately in starting and completing tasks related to the academic field and can be seen as a habit that causes discomfort, this phenomenon is called academic procrastination. 21 out of 33 grade X students of SMK Sunan Ampel experienced a high level of procrastination. The study aims to determine the effect of group counseling with reframing techniques on the academic procrastination of grade X students of SMK Sunan Ampel. Research is a type of quantitative research using the experimental method of one group pre-test pos-test design. The sample used in the study was 6 students who had a high level of academic procracination based on questionnaires. In research using questionnaires as a data collection method and data was analyzed using the SPSS application with the paired samples test formula. The results showed that there was an influence of group counseling with reframing techniques on the academic procrastination of grade X students of SMK Sunan Ampel.